(untitled) (Radiasi : Jurnal Berkala Pendidikan Fisika, 2023)
As science and technology advance, reform efforts in the utilization of technological outcomes in the learning process become more common. The goal of this study was to determine the efficacy of developing Audio-Visual-based Physics learning medium for use in Physics classes. ADDIE is the method that was used (Analyze, Design, Development, Implementation, Evaluation). Analyze (analyze) the contents of determining the test subject, the program that will be used to create films, and the reference material that will be collected. The content is designed (development). Making films, adjusting the data collection instrument to the aspects to be examined Storyboard (story sequence + visuals) as a physics learning medium produced based on the results of earlier analysis, Implementation (implementation) displays the contents on the subject using the Zoom meeting application. Development (development) includes product realization and validation for material specialists and media experts. Observation (evaluation) Data is gathered using data collecting instruments such as a questionnaire sheet for one material expert and one media expert, as well as answer questionnaires for 15 early-level SWCU Physics and Physics Education students on nuclear material, with a 75 percent affirmative response rate hypothesis. Data analysis that has been descriptively, qualitatively, and quantitatively processed. The results of a questionnaire to material and media experts were 94.17 percent, and the results of the questionnaire responses found 93.68 percent of all aspects, with the majority of the subjects stating that the audio-visual-based physics learning media that was created was worthy of being used as learning media.